Effect of Use of Swallow Dirt on the Growth and Yield of Peanut Soils on Ultisol Soils - Eduardus Fios; Surachman _; Elly Mustamir (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to determine the best dosage for growth and yield of peanut plants on ultisol soil. This research was carried out on the experimental field of the Faculty of Agriculture, Tanjungpura University of Pontianak which took place September 16, 2018 to December 20, 2018. The method used was a Complete Randomized Design Test (CRD) consisting of 6 treatments, 4 replications, and 4 samples. Giving various types of swallow droppings including a1 = 269 g / polybag, a2 = 514 g / polybag, a3 = 759 g / polybag, a4 = 1,004 g / polybag, a5 = 1,249 g / polybag and a6 = 1,494 g / polybag. Observations were made on plant height, number of pods of plants, dry weight of plants, dry weight of seeds. Based on the results of the study it can be concluded that the administration of swallow feces with a dose of 1,249 g / polybag or the equivalent of 16% organic matter gives the best results for the growth and yield of peanut plants on ultisol soil. Keywords: peanuts, swallow droppings, ultisol soil,